2006
DOI: 10.1007/s11427-006-2009-y
|View full text |Cite
|
Sign up to set email alerts
|

Glycine origin of the methyl substituent on C7′-N of octodiose for the biosynthesis of apramycin

Abstract: Apramycin is unique in the aminoglycoside family due to its octodiose moiety. However, either the biosynthesis process or the precursors involved are largely unknown. Addition of glycine, as well as serine or threonine, to the Streptomyces tenebrabrius UD2 fermentation medium substantially increases the production of apramycin with little effect on the growth of mycelia, indicating that glycine and/or serine might be involved in the biosynthesis of apramycin. The 13C-NMR analysis of [2-13C] glycine-fed (25% en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, only two genes in apr are annotated as encoding a transaminase (i.e., AprS and AprL), and both have already been assigned other functions. The alternative hypothesis is that C7′ and C8′ of 1 are derived from an amino acid such as glycine or a derivative thereof (Figure , path B) . However, early feeding experiments revealed that neither glycine nor serine is a precursor of carbon source to apramycin …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only two genes in apr are annotated as encoding a transaminase (i.e., AprS and AprL), and both have already been assigned other functions. The alternative hypothesis is that C7′ and C8′ of 1 are derived from an amino acid such as glycine or a derivative thereof (Figure , path B) . However, early feeding experiments revealed that neither glycine nor serine is a precursor of carbon source to apramycin …”
Section: Introductionmentioning
confidence: 99%
“…The alternative hypothesis is that C7′ and C8′ of 1 are derived from an amino acid such as glycine or a derivative thereof (Figure 2, path B). 29 However, early feeding experiments revealed that neither glycine nor serine is a precursor of carbon source to apramycin. 29 Recent results, however, have suggested a third possibility.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the antitumor compounds from marine drugs are derived from algal metabolites [3] and these metabolites play an important role in identification of new pharmaceutical compounds [4,5] . Actinomycetes are one of the most important sources for new bioactive compounds such as antibiotics and enzymes [6][7][8] which have diverse clinical effects against many pathogenic organisms viz., bacteria, fungi and parasite, etc. In fact, more than 60% of approved drugs are derived from natural compounds [9] in that, 50% of the natural antibiotics are produced from actinomycetes, among them marine actinomycetes have been reported to have antifungal, antibacterial and antiinflammatory activities [10] .…”
Section: Introductionmentioning
confidence: 99%